Paraganglioma of the Larynx - Dhakhwa, R; KC, Toran; Kafle, S; Lakhey, M (Journal of Pathology of Nepal, 2012)
Paraganglioma of the larynx is a rare tumor that arises from paraganglion cells. These tumors are generally considered benign and have to be differentiated from other neuroendocrine tumors. Diagnosis relies mostly on histopathologic examination followed by immunohistochemistry. Surgical excision generally confers complete cure of the tumor. We hereby present a case of laryngeal paraganglioma in a 60-yearold female, who underwent total laryngectomy following a diagnostic micro-laryngeal biopsy, which was supported by immunohistochemistry. DOI: http://dx.doi.org/10.3126/jpn.v2i3.6031 JPN 2012; 2(3): 245-247